Conceptual Study of Amavata : A Commonest Problem - Khadayata, Mayurika D; Shinde, B T; Bhausaheb, Suse Sandip; pandya, Harsh (International Research Journal of Ayurveda & Yoga, 2022)
Amavata is made up of two words Ama & vata, Ama means incomplete formation of Annarasa; It is Diseases of Rsavahastrotas, when aggravated Vata & Ama combine Pathogenesis of Amavata Occurs. Clinical Features include Swelling & Stiffness of joints, fever & Pain. These symptoms related to Rheumatological arthritis. Due to It`s chronicity, incurability, complication, it is a challenging disease. Many allopathic drugs are prescribed for this but they give only Symptomatic relief. Ayurveda play major role here. The treatment procedure described are langhana, swedana, dipana, virechana, Basti.